IMPROVING THE STUDENTS ACHIEVEMENT IN SPEAKING THROUGH TEAMS-GAMES-TOURNAMENT TECHNIQUE - Ramadhayani Fitri Nasution and Busmin Gurning (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
The objective of this study was to investigate whether the application of Teams-Games-Tournament Technique improve the students achievement in Speaking. This study was an classroom action research. The subject of this study was class XI IPA 3 SMA Muhammadiyah 8 Kisaran which consists of 35 students. The study was conducted in two cycles, cycle I consisted of three meetings and cycle II was consisted of three meetings. The instruments for collecting data were quantitative (oral speaking test) and qualitative data (observation sheet and diary note). Based on speaking scores, students’ score kept improving in every evaluation and based on observation sheet and diary note, it was found that teaching and learning process ran well. Students could enlarge their thinking process. The result of this study showed that Teams-Games-Tournament improved students’ achievement in speaking.